A high-strength lead-zinc pellet and a method for producing the pellet using lead-zinc ash
By preparing high-strength lead-zinc pellets and applying them to the lead-zinc smelting process, the problem of unrecycled by-products is solved, and efficient resource utilization and optimization of smelting process are achieved.
Patent Information
- Application Number
- CN202310366632.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-04-07
AI Technical Summary
During the existing lead-zinc smelting process, the unreduced zinc oxide, refill powder, scum, orchid powder, electro-dust ash and other materials in the by-products are not effectively recycled, resulting in waste of resources and sintering cycles.
High-strength lead-zinc pellets are prepared by uniformly mixing 92.5%-95% lead-zinc raw materials and 5%-7.5% binder, and specific raw material ratios and process flows, including raw material ingredients, mixing, press molding and drying, to produce pellets.
The high strength and high temperature stability of lead-zinc pellets are achieved, the sintering cycle is avoided, the lead-zinc production is improved, the energy consumption is reduced, and the lead-containing zinc ash slag is effectively recovered and utilized, reducing environmental pollution.
Smart Images

Figure CN116287864B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metallurgy, and relates to a technology for recycling lead-zinc smelting ash, and specifically relates to a high-strength lead-zinc pellet and a method for producing the pellet using the lead-zinc ash. Background Art
[0002] In the nonferrous metallurgical industry, the closed blast furnace smelting method is a mainstream pyrometallurgical lead and zinc smelting technology. It mainly uses carbonaceous reducing agents to reduce zinc and lead from the sintered blocks of lead and zinc concentrate. Zinc vapor condenses into zinc in the lead rain condensation. Lead and slag enter the furnace and are separated from lead by the electric heating front bed. In this production process, a large number of by-products are produced, including zinc oxide, return powder, slag, blue powder, electrostatic precipitator ash and other main lead and zinc materials that are not completely reduced. At present, most manufacturers use physical stamping to block the by-products, and the stamped blocks are returned to the sintering batching section for re-sintering. The lead-zinc blocks physically stamped out have poor hot strength, and the sintered blocks melt prematurely in the subsequent smelting process. The zinc vapor cannot be completely precipitated, the lead and zinc output is small and the slag volume is large. There are also a large number of recyclable lead and zinc elements in the slag, which directly wastes resources by treating it as solid waste. If the slag is stamped into blocks again and used as a sintering batching raw material, a sintering cycle will be formed. This treatment method wastes manpower, material resources and resources. Therefore, it is necessary to improve the recycling method of lead-zinc dust and slag. Summary of the invention
[0003] In view of this, one of the objects of the present invention is to provide a high-strength lead-zinc pellet.
[0004] The technical solution is as follows:
[0005] A high-strength lead-zinc pellet is formed by uniformly mixing 92.5%-95% lead-zinc raw materials and 5%-7.5% binder in parts by weight;
[0006] In terms of weight, the lead-zinc raw material includes 20%-30% zinc oxide, 15%-25% roasted sand, and the rest is lead-zinc ash;
[0007] The lead-zinc ash slag is any one of blue powder, electrostatic precipitator ash, floating slag and return powder, or a combination of several of them.
[0008] In one embodiment, the compressive strength of the lead-zinc pellets is above 1200N when the moisture content is dried to <2%.
[0009] In one embodiment, the weight ratio of lead and zinc elements in the lead-zinc raw material is 1:(1.8-2.3), preferably 1:(1.95-2.1).
[0010] In one embodiment, the adhesive comprises, by weight, 15%-25% pregelatinized starch, 4%-6% polyvinyl alcohol, 20%-30% liquid sodium lignin sulfonate, 12%-18% sodium silicate and 30%-40% clay.
[0011] In one embodiment, the binder includes 18%-23% pregelatinized starch, 4%-6% polyvinyl alcohol, 23%-26% liquid sodium lignin sulfonate, 13%-17% sodium silicate, and 33%-37% clay.
[0012] A second object of the present invention is to provide a method for producing pellets using lead-zinc ash.
[0013] The technical solution is as follows:
[0014] A method for producing any of the above-mentioned pellets using lead-zinc ash, the key steps of which are:
[0015] S1, raw material batching: obtaining each component of the lead-zinc raw material, and determining the content of lead and zinc in each component, and batching each raw material component according to a certain mass ratio to obtain material A, so that the lead-zinc content ratio in the material A is 1:(1.8-2.3);
[0016] S2, mixing: uniformly mixing the material A with a binder and water to obtain a material B;
[0017] S3, pressing and molding: pressing the material B into cold pressed balls;
[0018] S4, drying: drying the cold pressed balls to obtain finished pellets.
[0019] In one embodiment, the step S2 specifically includes firstly stirring and mixing the material A, and then adding the binder and water and continuing to stir evenly.
[0020] In one embodiment, the above step S3 includes:
[0021] S31, pre-pressing and molding: feeding the material B into a pre-pressing and ball pressing machine for preliminary shaping and fixing to obtain material C;
[0022] S32, ball pressing: material C is sent to a finished product ball pressing machine for final pressing and molding to obtain material D containing wet powder and molded cold-pressed balls.
[0023] In one embodiment, the above step S4 is specifically as follows:
[0024] The cold pressed balls in the material D are sent to a dryer for drying at a temperature of 80-100° C. to obtain a material E containing dry powder and dry cold pressed balls.
[0025] In one embodiment, the step S32 further includes screening out the wet powder in the material D and returning it to be fed into the pre-pressing ball press together with the material B;
[0026] The step S4 also includes screening out the dry powder in the material E and returning it for raw material batching. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the production process flow chart of lead-zinc pellets. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with embodiments and drawings.
[0029] A high-strength lead-zinc pellet is formed by uniformly mixing 92.5%-95% lead-zinc raw materials and 5%-7.5% binder by weight; the lead-zinc raw materials include 20%-30% zinc oxide, 15%-25% roasted sand, and the rest is lead-zinc ash. The lead-zinc ash is any one or a combination of blue powder, electrostatic precipitator ash, scum and return powder. These lead-zinc ash can be by-products produced in general non-ferrous metal smelting processes, such as those produced by closed blast furnace smelting. According to the type, weight and lead-zinc content of the by-products in the actual production process of the enterprise, they can be flexibly matched to maximize the utilization of the by-products.
[0030] In order to meet the effect of pellet smelting, the compressive strength of lead-zinc pellets with a maximum size of 30-40 mm should be above 1200N when dried to a moisture content of <2%. Selecting an appropriate binder can make the pellets meet this performance indicator.
[0031] The composition of a type of adhesive is: by weight, it includes 15%-25% pregelatinized starch, 4%-6% polyvinyl alcohol, 20%-30% liquid sodium lignin sulfonate, 12%-18% sodium silicate and 30%-40% clay. This adhesive combines organic adhesive components and inorganic adhesive components, and achieves the desired effect through appropriate proportions, so that the lead-zinc raw materials have good balling properties, high strength and good porosity. Among them, pregelatinized starch mainly plays a material bonding role, and polyvinyl alcohol is used in combination with pregelatinized starch to increase viscosity and increase the hardness of the pellets after solidification. Due to the use of powdered materials such as zinc oxide, blue powder, and electrostatic precipitator ash, liquid sodium lignin sulfonate is easy to penetrate, has good fluidity, and has a certain viscosity. Sodium silicate is an inorganic adhesive. Clay has a certain viscosity and good hot strength. More preferably, the binder comprises 18%-23% pregelatinized starch, 4%-6% polyvinyl alcohol, 23%-26% liquid sodium lignin sulfonate, 13%-17% sodium silicate and 32%-37% clay.
[0032] The pellet preparation process and technical effects of the present invention are explained with specific examples.
[0033] Pellet preparation
[0034] Example 1
[0035] like Figure 1 , a method for producing pellets using lead-zinc ash, the steps are:
[0036] S1, raw material ratio: the raw materials in this embodiment include zinc oxide, return powder, scum, blue powder, electrostatic precipitator ash and roasted sand. The zinc content in zinc oxide is measured respectively, and the content of lead and zinc in return powder, scum, blue powder, electrostatic precipitator ash and roasted sand is measured. The ingredients are prepared according to the lead-zinc content ratio of 1:1.8, and the ratio of each component is calculated according to the lead and zinc content in each raw material. After zinc oxide, scum and electrostatic precipitator ash are proportioned according to the calculated mass ratio, they are stored in No. 1 silo using a crane grab, blue powder and return powder are stored in No. 2 silo, and roasted sand is stored in No. 3 silo. The raw materials are proportioned according to the designed mass ratio to obtain material A. Specifically, the proportions of each raw material are: zinc oxide content is 20%, return powder content is 15%, scum content is 10%, blue powder content is 15%, electrostatic precipitator ash content is 15%, and roasted sand content is 25%.
[0037] The designed usage of material A and adhesive are 92.5% and 7.5% respectively.
[0038] S2, mixing: adding binder and water to material A and feeding into a mixer for stirring and mixing to obtain material B.
[0039] In this embodiment, weighing belt conveyors are provided between the No. 1 silo, No. 2 silo, and No. 3 silo and the mixer, which is convenient for weighing various raw materials according to the raw material ratio, and can improve production efficiency. In addition, an intermediate silo is provided between the No. 1 silo, No. 2 silo, and No. 3 silo and the mixer, which is convenient for providing storage space for materials before stirring and mixing, reducing the mixing pressure, and also convenient for continuous production and reducing the energy consumption caused by the start and stop of equipment. The adhesive of this embodiment is stored in the adhesive silo, and a water silo for storing water is also provided, wherein a weighing belt conveyor is also provided between the adhesive silo and the mixer, which is convenient for weighing the adhesive, and a weighing system is also provided between the water silo and the mixer, which is convenient for weighing it.
[0040] In this embodiment, the adhesive composition is: 15% pregelatinized starch, 6% polyvinyl alcohol, 30% liquid sodium lignin sulfonate, 12% sodium silicate and 37% clay.
[0041] S3, compression molding, includes two steps:
[0042] S31, pre-pressing and molding: feeding material B into the pre-pressing and briquetting machine for preliminary shaping and fixing, so as to form material C with a certain shape and structure, which is conducive to improving the subsequent ball forming rate. Specifically, the mixer and the pre-pressing and briquetting machine of this embodiment are connected by a belt conveyor;
[0043] S32, ball pressing: feeding material C into a finished product ball pressing machine for final pressing and molding to obtain material D containing wet powder and molded cold pressed balls;
[0044] After the material C is pressed and shaped, the material D obtained will contain unformed wet powder with a certain amount of moisture. In order to improve the utilization rate of the raw materials, the wet powder is sieved through a vibrating screen and dropped onto a return belt conveyor, and then re-conveyed to the pre-pressing briquetting machine for pre-pressing treatment;
[0045] S4, drying: a belt conveyor is used to connect the finished product ball press machine and the dryer, and the formed cold-pressed balls are sent to the dryer for drying. The dryer of this embodiment includes a burner, a dryer main body, and an air supply and dehumidification fan. The burner heats the air and sends it to the dryer main body to dry the cold-pressed balls, so as to obtain material E containing dry powder and dry cold-pressed balls, and the dry powder is screened out and returned to the lead-zinc raw material. Specifically, the dryer of this embodiment adopts a flap dryer, which is provided with a drying chain belt, and the chain belt is provided with sieve holes, which can screen out the dry powder, and a belt conveyor is provided under the chain belt for transporting the dry powder back to the No. 2 silo. When the drying is completed, the dry powder obtained after drying is transported back to the No. 2 silo for storage, so that it can be re-proportioned and subjected to subsequent mixing and ball pressing processes. The temperature of the dryer is controlled at 80-100°C during drying, and the drying time is 4-7 hours. The moisture content of the formed cold-pressed balls after drying is no more than 2.0%, and they can be sent to the finished product area for storage or directly transported to the blast furnace for use.
[0046] Example 2
[0047] A method for producing pellets using lead-zinc ash, the production process is the same as that of Example 1, except that the raw materials and the proportions are:
[0048] The raw materials include zinc oxide, return powder, scum, electrostatic precipitator ash and roasted sand. After respectively measuring the content of lead and zinc in the return powder, scum, electrostatic precipitator ash and roasted sand, the materials are mixed according to the lead-zinc content ratio of 1:1.95, and the proportion of each component is calculated according to the content of lead and zinc in each raw material. After zinc oxide, scum and electrostatic precipitator ash are proportioned according to the calculated mass ratio, they are stored in silo No. 1 using a crane grab bucket, and the return powder and roasted sand are stored in silo No. 2 and silo No. 3, respectively. The raw materials are proportioned according to the designed mass ratio to obtain material A. Specifically, the proportions of each raw material are: zinc oxide content is 25%, electrostatic precipitator ash content is 20%, scum content is 20%, return powder content is 20%, and roasted sand content is 15%.
[0049] The designed dosage of material A and adhesive is 95% and 5% respectively. In this embodiment, the adhesive composition is: 18% pregelatinized starch, 4% polyvinyl alcohol, 20% liquid sodium lignin sulfonate, 18% sodium silicate and 40% clay.
[0050] Example 3
[0051] A method for producing pellets using lead-zinc ash, the production process is the same as that of Example 1, except that the raw materials and the proportions are:
[0052] The raw materials include zinc oxide, return powder, scum, electrostatic precipitator ash and roasted sand. After respectively measuring the content of lead and zinc in the return powder, scum, electrostatic precipitator ash and roasted sand, the materials are mixed according to the lead-zinc content ratio of 1:2.1, and the proportion of each component is calculated according to the content of lead and zinc in each raw material. After zinc oxide, scum and electrostatic precipitator ash are mixed according to the calculated mass ratio, they are stored in silo No. 1 using a crane grab bucket, and the return powder and roasted sand are stored in silo No. 2 and silo No. 3, respectively. The raw materials are mixed according to the designed mass ratio to obtain material A. Specifically, the proportions of each raw material are: zinc oxide content is 30%, electrostatic precipitator ash content is 15%, scum content is 15%, return powder content is 20%, and roasted sand content is 20%.
[0053] The designed dosage of material A and adhesive is 95% and 5% respectively. In this embodiment, the adhesive composition is: 23% pregelatinized starch, 4% polyvinyl alcohol, 26% liquid sodium lignin sulfonate, 13% sodium silicate and 34% clay.
[0054] Example 4
[0055] A method for producing pellets using lead-zinc ash, the production process is the same as that of Example 1, except that the raw materials and the proportions are:
[0056] The raw materials include zinc oxide, return powder, blue powder, electrostatic precipitator ash and roasted sand. After respectively determining the contents of lead and zinc in the return powder, blue powder, electrostatic precipitator ash and roasted sand, the materials are mixed according to the lead-zinc content ratio of 1:2.1, and the proportion of each component is calculated according to the lead and zinc content in each raw material. After zinc oxide, blue powder and electrostatic precipitator ash are mixed according to the calculated mass ratio, they are stored in silo No. 1 using a crane grab, and the return powder and roasted sand are stored in silo No. 2 and silo No. 3, respectively. The raw materials are mixed according to the designed mass ratio to obtain material A. Specifically, the proportions of each raw material are: zinc oxide content is 30%, blue powder content is 18%, electrostatic precipitator ash content is 12%, return powder content is 20%, and roasted sand content is 20%.
[0057] The designed dosage of material A and adhesive is 95% and 5% respectively. In this embodiment, the adhesive composition is: 25% pregelatinized starch, 5% polyvinyl alcohol, 23% liquid sodium lignin sulfonate, 17% sodium silicate and 30% clay.
[0058] Example 5
[0059] A method for producing pellets using lead-zinc ash, the production process is the same as that of Example 1, except that the raw materials and the proportions are:
[0060] The raw materials include zinc oxide, electrostatic precipitator ash, return powder, slag and roasted sand. After respectively measuring the content of lead and zinc in the return powder, slag, electrostatic precipitator ash and roasted sand, the materials are mixed according to the lead-zinc content ratio of 1:2.3, and the proportion of each component is calculated according to the content of lead and zinc in each raw material. After zinc oxide, slag and electrostatic precipitator ash are mixed according to the calculated mass ratio, they are stored in silo No. 1 using a crane grab bucket, and the return powder and roasted sand are stored in silo No. 2 and silo No. 3, respectively. The raw materials are mixed according to the designed mass ratio to obtain material A. Specifically, the proportions of each raw material are: zinc oxide content is 30%, slag content is 20%, electrostatic precipitator ash content is 20%, return powder content is 15%, and roasted sand content is 15%.
[0061] The designed dosage of material A and adhesive is 95% and 5% respectively. In this embodiment, the adhesive composition is: 25% pregelatinized starch, 4% polyvinyl alcohol, 21% liquid sodium lignin sulfonate, 18% sodium silicate and 32% clay.
[0062] Pellet performance test
[0063] Finished pellet samples prepared in different embodiments were randomly selected to test the compressive strength and determine the 1000°C pulverization index.
[0064] Compressive strength: Referring to the test method of the International Organization for Standardization (ISO4700-1983), a single pellet is placed between the two pressing plates of the press and a load is applied until it breaks.
[0065] Pulverization index: refer to the international standard ISO4696-1984 "Method of using cold drum after static reduction for low temperature pulverization test of iron ore", except that the test temperature in this embodiment is 1000°C. Take the pellet sample and place it in a fixed bed, and statically reduce it with a reducing gas composed of CO, CO2 and N2 at a temperature of 1000°C. After reduction for 1 hour, cool the sample to below 100°C, rotate it with a small drum for a total of 300 revolutions, and then screen it with a square hole sieve with a hole width of 6.30mm, 3.15mm and 0.5mm. The reduction pulverization index is used to represent the pulverization degree of the iron ore.
[0066] Take the lead-zinc pellets prepared in Examples 1 to 3 respectively, and randomly take 5 samples from each group for compression test. During the test, the pressing plate is pressed at a rate of 20 mm / min. The compressive strength and pulverization index are shown in Tables 1 and 2 respectively. The average compressive strength of the cold-pressed pellets is above 1300N, and the pulverization index at 1000℃ is relatively high, which meets the smelting requirements.
[0067] Table 1 Compressive strength of lead-zinc pellet samples
[0068]
[0069] Table 2 Powdering index of lead-zinc pellets at 1000℃
[0070]
[0071] Actual smelting effect of pellets
[0072] Experimental studies have found that the weight ratio of lead and zinc elements in the lead-zinc raw material is preferably 1: (1.8-2.3), preferably 1: (1.95-2.1). This is because, if it is greater than this ratio, the zinc content is too high, and the pellets will be pulverized prematurely during the smelting process; if it is less than this ratio, the lead content is too high, and the pellets will affect the precipitation of zinc vapor during the smelting process. Controlling the lead and zinc content in the pellets at this ratio can, on the whole, make the lead and zinc yield higher. Therefore, the pellets prepared in Examples 1 to 5 all control the lead and zinc ratio in the raw materials within this range.
[0073] The lead-zinc cold-pressed pellets prepared by the method of the present invention meet various performance requirements. 6% by weight of pellets were added to the blast furnace of a smelter in a certain group company, and a total of 2,500 tons of lead-zinc pellets were used, and the furnace condition was smooth. Prior to this, the smelting by-products were sintered again by punching into blocks. After adding 6% of pellets, the average daily output of lead and zinc increased by 2-3 tons each compared to before the addition of lead-zinc pellets, which effectively avoided the sintering cycle while increasing the lead and zinc output, reducing energy consumption and bringing better economic benefits.
[0074] The beneficial effects of the present invention are as follows: the lead-zinc pellets of the present invention have the characteristics of high compressive strength and are not easy to pulverize at high temperature. The finished pellets can directly enter a closed blast furnace to participate in lead-zinc smelting production, providing high-quality raw materials for the closed blast furnace; the lead-zinc ash by-products generated in the lead-zinc smelting process are used to produce pellets, which recovers valuable elements zinc and lead, reduces environmental dust pollution, and also reduces the problem of sintered blocks entering the sintering machine for re-firing, thereby achieving emission reduction and consumption reduction, and realizing efficient utilization of by-products generated in the traditional lead-zinc smelting process.
[0075] Finally, it should be noted that the above description is only a preferred embodiment of the present invention. Under the guidance of the present invention, ordinary technicians in this field can make various similar expressions without violating the purpose and claims of the present invention, and such changes all fall within the scope of protection of the present invention.
Claims
1. A high-strength lead-zinc pellet, characterized in that: It is formed by uniformly mixing 92.5%-95% lead-zinc raw materials and 5%-7.5% binder in parts by weight; In terms of weight, the lead-zinc raw material includes 20%-30% zinc oxide, 15%-25% roasted sand, and the rest is lead-zinc ash; The lead-zinc ash slag is any one or a combination of blue powder, electrostatic precipitator ash, floating slag and return powder; The lead-zinc pellets have a compressive strength of more than 1200N when dried to a moisture content of less than 2%; In terms of weight, the adhesive comprises 15%-25% pregelatinized starch, 4%-6% polyvinyl alcohol, 20%-30% liquid sodium lignin sulfonate, 12%-18% sodium silicate and 30%-40% clay.
2. The high-strength lead-zinc pellet according to claim 1, characterized in that: The weight ratio of lead and zinc elements in the lead-zinc raw material is 1:(1.8-2.3).
3. The high-strength lead-zinc pellet according to claim 2, characterized in that: The weight ratio of lead and zinc elements in the lead-zinc raw material is 1:(1.95-2.1).
4. The high-strength lead-zinc pellet according to claim 1, characterized in that: The adhesive comprises 18%-23% pregelatinized starch, 4%-6% polyvinyl alcohol, 23%-26% liquid sodium lignin sulfonate, 13%-17% sodium silicate and 33%-37% clay.
5. A method for producing pellets as claimed in any one of claims 1 to 4 using lead-zinc ash, characterized in that The steps are: S1, raw material batching: obtaining each component of the lead-zinc raw material, and determining the content of lead and zinc in each component, and batching each raw material component according to a certain mass ratio to obtain material A, so that the lead-zinc content ratio in the material A is 1:(1.8-2.3); S2, mixing: uniformly mixing the material A with a binder and water to obtain a material B; S3, pressing and molding: pressing the material B into cold pressed balls; S4, drying: drying the cold pressed balls to obtain finished pellets.
6. The method according to claim 5, characterized in that: Specifically, the step S2 is to initially stir and mix the material A, and then add the binder and water and continue to stir evenly.
7. The method according to claim 5, characterized in that The step S3 comprises: S31, pre-pressing and molding: feeding the material B into a pre-pressing and ball pressing machine for preliminary shaping and fixing to obtain material C; S32, ball pressing: material C is sent to a finished product ball pressing machine for final pressing and molding to obtain material D containing wet powder and molded cold-pressed balls.
8. The method according to claim 7, characterized in that: The step S4 is specifically as follows: The cold pressed balls in the material D are sent to a dryer for drying at a temperature of 80-100° C. to obtain a material E containing dry powder and dry cold pressed balls.
9. The method according to claim 8, characterized in that: The step S32 also includes screening out the wet powder in the material D and returning it to the pre-pressing ball press together with the material B; The step S4 also includes screening out the dry powder in the material E and returning it for raw material batching.
Citation Information
Patent Citations
Lead-zinc slag pelletizing process
CN106498156A